2012
DOI: 10.1002/bmc.2791
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability studies for tributyltin determination in human urine samples using headspace solid‐phase microextraction and gas chromatography mass spectrometry

Abstract: A headspace solid-phase micro-extraction (HS-SPME) method was employed in order to study the effect of storage conditions of human urine samples spiked with tributyltin (TBT) using gas chromatography and mass spectrometry. To render the analyte more volatile, the derivatization (ethylation) was made in situ by sodium tetraethylborate (NaBEt(4) ), which was added directly to dilute unpreserved urine samples and in buffers of similar acidity. The stability of TBT in human urine matrix was compared with the stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Zachariadis et al 21 investigated the stability of TBT in human urine and found that storage at 4 or À20 C was possible for no more than 2 days. Thereaer, greater variation was seen in those maintained at 4 C compared to À20 C. Losses were also noted following freeze-thaw cycles.…”
Section: Collection and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Zachariadis et al 21 investigated the stability of TBT in human urine and found that storage at 4 or À20 C was possible for no more than 2 days. Thereaer, greater variation was seen in those maintained at 4 C compared to À20 C. Losses were also noted following freeze-thaw cycles.…”
Section: Collection and Storagementioning
confidence: 99%
“…Sunday et al 15 presented a detailed review of the chemical speciation of organotin compounds in environmental and biological matrices. Zachariadis et al 21 investigated the effect of storage conditions on the stability of tributyltin (TBT) species in human urine. Spiked urine and buffer samples were stored at 4 C and À20 C for up to one month.…”
Section: Rare Earth Elementsmentioning
confidence: 99%
“…Sunday et al 15 presented a detailed review of the chemical speciation of organotin compounds in environmental and biological matrices. Zachariadis et al 21 investigated the effect of storage conditions on the stability of tributyltin (TBT) species in human urine. Spiked urine and buffer samples were stored at 4 C and À20 C for up to one month.…”
Section: Rare Earth Elementsmentioning
confidence: 99%